Quantum State Resolved Studies of Gas/Surface Reaction Dynamics - Rainer D. Beck; Thomas R. Rizzo (CHIMIA, 2004)
Laser light is an invaluable tool for detailed experimental studies of chemical reactions. The ability to prepare reagent molecules in specific quantum states and to resolve the quantum state distribution of reaction products using laser radiation has been key to the field of chemical reaction dynamics, which studies chemistry at a fundamental microscopic level. Today, state-resolved experiments are common for unimolecular and bi-molecular reactions in the gas phase, but equivalent measurements for gas/surface reactions have only recently started to appear. This contribution reviews the methodology developed in our group at the EPFL for the quantum state resolved investigation of molecule/surface reactions and gives representative results on the dissociative chemisorption of methane on single crystal nickel surfaces.